Estudo numérico bidimensional de propagação de trincas em ferro fundido nodular austemperado (adi) - Franca, Gustavo Von Zeska de (2019)
The austempered ductile iron (ADI) has a wide range of applications, due to its high mechanical strength, fatigue resistance and wear resistance. ADI is composed by an ausferritic matrix with graphite nodules. The nodules have strength lower than the matrix and can act as stress concentrators that nucleate cracks. The nodules also influence on cracks through changing its trajectory that are deflected in the nodules direction and may generate a protective effect. However, according to the literature, the crack propagation mechanism is not yet fully understood. In this context, this work presents a bidimensional numerical model to simulate a crack propagation on ADI material subjected to cyclic load which results crack opening in traction and shear mode combined on the crack tip. The model was implemented in Python language and uses the commercial finite element code ABAQUS, along with a routine for crack growth calculation, based on Paris law, to simulate its propagation. It was found that the main parameter responsible for changing the crack direction is the stress intensity factor in mode II, that is, the shear that occurs at the crack tip. The simulations showed that the presence of the nodule generates a shear load on the crack tip and causes it to be directed to the nodule itself. Modifications such as increasing nodule size and decreasing nodule distance to crack tip intensify this action. It was also found that, in simulations with two different ADI materials with the same graphite area fraction, increasing the number of nodules causes the crack to have a shorter lifetime until it intercepts a new nodule. Therefore, this suggests that the protective effect of nodules in ADI material may be correlated with the number of intercepted nodules and the energy for nucleating new cracks.